THE EFFECT OF PERSONAL TAX EXEMPTION ON FERTILITY IN INDONESIA - Khurria, Arima; Handayani, Dwini (Universitas Airlangga, 2024)
Personal tax exemption (Penghasilan Tidak Kena Pajak - PTKP) can influence fertility choices by changing the costs or benefits of childbearing and increasing family disposable income. This study aims to investigate the impact of personal tax exemption on the addition of children in Indonesia. This study employs secondary data from Indonesian Family Life Survey (IFLS) data waves 4 and 5. The estimation, using a linear probability model, is an improvement from earlier studies as it employs a non-linear specification to more effectively capture the pattern of children's desired demand. This study found an inverse U-shaped relationship between the addition of children and personal tax exemption. The inverse U-shaped relationship indicates that the marginal effect of personal tax exemption decreases as the value of personal tax exemption increases. In addition, the probability of adding children is also influenced by the mother’s characteristics (age and working status), other adult female family members in the household, and the number of children. This study reveals that the taxation variable, personal tax exemption, can affect fertility. Thus, birth control should be carried out by considering various aspects other than direct birth control (e.g., family planning), including taxation.